Mississippi blood [compact disc, unabridged] : a novel - Iles, Greg (Harper Audio, 2017)
Grief-stricken and with his world collapsing around him, Penn Cage is shut out of trial preparations by his once-revered Southern doctor father, who is about to be tried for murder in the wake of revelations about a mixed-race child and KKK associations.